Life Cycle Assessment of Municipal Solid Waste Management Strategies in Babolsar: Evaluating Environmental Impacts and Energy Consumption - Babak Sheydaei; Gholamreza Nabi; Fatemeh Yazdian (Environmental Energy and Economic Research)
Municipal solid waste management (MSWM) is a critical challenge in rapidly urbanizing cities, especially in coastal areas like Babolsar, Iran. This study aims to evaluate the environmental impacts of various MSWM scenarios using the Life Cycle Assessment (LCA) methodology with the IWM-2 model. Seven scenarios were examined, ranging from landfilling without energy recovery to advanced combinations incorporating composting, recycling, and energy recovery. Data were sourced from the Babolsar City Municipality, encompassing waste generation, composition, and current management practices. The results indicate significant differences in environmental impacts across scenarios. Scenario 1 (100% landfilling) exhibited the highest environmental burdens, including greenhouse gas emissions and toxic outputs. In contrast, Scenarios 4, 5, and 6, which integrate composting, recycling, and energy recovery, demonstrated substantial reductions in these impacts. Specifically, Scenario 6 emerged as the most environmentally favorable option, significantly lowering greenhouse gas emissions and energy consumption. These findings highlight the importance of a diversified waste management strategy that incorporates multiple treatment methods to minimize environmental impacts. The study's comprehensive assessment provides valuable insights for decision-makers and policymakers aiming to enhance sustainability in urban waste management systems. The implications of these findings extend to similar urban areas seeking to optimize their waste management practices for better environmental outcomes.